2020
DOI: 10.1093/clinchem/hvz022
|View full text |Cite
|
Sign up to set email alerts
|

Protein Biomarker Quantification by Immunoaffinity Liquid Chromatography–Tandem Mass Spectrometry: Current State and Future Vision

Abstract: Immunoaffinity–mass spectrometry (IA-MS) is an emerging analytical genre with several advantages for profiling and determination of protein biomarkers. Because IA-MS combines affinity capture, analogous to ligand binding assays (LBAs), with mass spectrometry (MS) detection, this platform is often described using the term hybrid methods. The purpose of this report is to provide an overview of the principles of IA-MS and to demonstrate, through application, the unique power and potential of this technology. By c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 157 publications
0
64
0
Order By: Relevance
“…Several studies have suggested prognostic factors for LUSCC, including proteins, mRNAs, lncRNAs and miRNAs. Tumor protein biomarkers demonstrated important roles in cancer detection, clinical outcome prediction or effective therapy selection [7][8][9]. Of note, protein biomarkers are…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested prognostic factors for LUSCC, including proteins, mRNAs, lncRNAs and miRNAs. Tumor protein biomarkers demonstrated important roles in cancer detection, clinical outcome prediction or effective therapy selection [7][8][9]. Of note, protein biomarkers are…”
Section: Introductionmentioning
confidence: 99%
“…Immunoaffinity LC/MS/MS is an emerging analytical platform in the analysis of protein biomarker studies as it combines the advantage of immuno‐capture to enrich analyte quantities with high specificity of detection of multiple surrogate peptides 22 . This study describes several key elements that are needed for the accurate determination of PD1 and PD‐L1 levels in human tumor tissues by IA‐LC/MS.…”
Section: Resultsmentioning
confidence: 99%
“…Used separately, they can generate variations in the results they produce [ 32 ]. Conversely, the merging of solid-phase extraction (SPE)/affinity-capture with chromatographic or electrophoretic methods, allows for isolation, concentration, separation, detection, quantification, and characterization of individual target biomarkers and/or structurally related analytes [ 25 , 33 , 34 ]. Moreover, coupling on-line solid-phase extraction methods to HPLC or CE instruments have been shown to provide many advantages, including speed of analysis and reproducibility of results, particularly, when antibodies, aptamers, and/or lectins have been used for the isolation and concentration of target analytes.…”
Section: Brief History Of Biomarker-assay Technologiesmentioning
confidence: 99%
“…The superior resolution power of CE permits the separation of closely structurally related analytes. Significant improvements in the analysis of biomarkers can also be achieved when powerful detectors, such as laser-induced fluorescence detection and/or mass spectrometry, are used for their detection and characterization [ 25 , 34 ].…”
Section: Brief History Of Biomarker-assay Technologiesmentioning
confidence: 99%